Optimation Free Space Optic (FSO) Design with Kim Model Using Space Diversity - Triyono Subekti; Anggun Fitrian Isnawati; Dodi Zulherman (JURNAL INFOTEL, 2019)
The development of communication services in remote rural areas is difficult to use cable-based systems such as Digital Subscriber Line (DSL) and FTTx. One solution to solve this problem is to use a wireless system such as radio communication. Free Space Optic (FSO) communication system is a better choice compared to radio communication because of the flexibility of frequency usage. One of the problems of the FSO communication system is the range not too far. The range of the FSO can be increased by using the space diversity method. This study compared FSO systems that not use space diversity and FSO systems that use space diversity in three weather conditions, namely clear, haze, and fog. In taking data results using Kim model propagation with variations in the range between 100 – 2000 meters. The modulation used in this study is external modulation. The result of the analysis of FSO performance after adding space diversity, the range of FSO increases as far as 1200 meters when the condition is clear. During the haze condition, the FSO range increase as far as 800 meters. During the fog condition, the FSO range has increased as far as 300 meters. By adding space diversity, the Q-factor value has increased, and BER (Bit Error Rate) has decreased.